Pinjaman Online, Konsumerisme, dan Krisis Finansial Generasi Z - Poernama, Sandra Aulia; Achdiani, Yani; Abdullah, Mirna Nur Alia (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of lifestyle, personality, and financial literacy on the behavior of online loan usage among Generation Z in Indonesia. The research employs a library research method to examine the impact of online loans on the financial and social behavior of Generation Z. This method allows the researcher to access and synthesize various relevant academic sources comprehensively. Data were obtained from scientific articles, accredited journals, conference proceedings, and research reports published between 2020 and 2025, focusing on issues such as online loans, consumer lifestyle, financial literacy, and the characteristics of Generation Z. The analysis was conducted descriptively and thematically to identify patterns, differences, and similarities across studies, and to formulate strategic recommendations based on the synthesized literature. The findings reveal that the use of online loans by Generation Z in Indonesia affects various aspects, including financial, social, and psychological domains. Key factors driving irresponsible borrowing include the ease of digital access, low financial literacy, and a consumerist lifestyle. Generation Z tends to use online loans for non-productive needs without considering their repayment capacity, leading to personal financial crises. Furthermore, social pressure from digital media and the phenomenon of Fear of Missing Out (FoMO) exacerbate the situation, impacting mental health and social relationships. These findings highlight the urgent need for financial education and stricter regulations on fintech services to create a healthy and sustainable digital financial ecosystem for the younger generation.